2009
DOI: 10.1128/aac.01626-08
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Vaccinia Virus Replication by Two Small Interfering RNAs Targeting B1R and G7L Genes and Their Synergistic Combination with Cidofovir

Abstract: In view of the threat of the potential use of variola virus in a terrorist attack, considerable efforts have been performed to develop new antiviral strategies against orthopoxviruses. Here we report on the use of RNA interference, either alone or in combination with cidofovir, as an approach to inhibit orthopoxvirus replication. Two selected small interfering RNAs (siRNAs), named siB1R-2 and siG7L-1, and a previously reported siRNA, i.e., siD5R-2 (which targets the viral D5R mRNA), were evaluated for antivira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 73 publications
2
16
1
Order By: Relevance
“…It is unclear if these two activities are related, but the activity of this compound did not translate into animal models of infection (Smee et al, 2010). The inhibition of B1R and G7L expression by siRNA has also been reported that results in significant reductions in the replication of vaccinia virus (Vigne et al, 2009). …”
Section: Potential Molecular Targets In Orthopoxvirus Replication mentioning
confidence: 96%
“…It is unclear if these two activities are related, but the activity of this compound did not translate into animal models of infection (Smee et al, 2010). The inhibition of B1R and G7L expression by siRNA has also been reported that results in significant reductions in the replication of vaccinia virus (Vigne et al, 2009). …”
Section: Potential Molecular Targets In Orthopoxvirus Replication mentioning
confidence: 96%
“…In this regard, however, it is worth noting that a single envelope trimer is sufficient for HIV entry (46). Several recent studies indicated that siRNAs can inhibit VACV replication, although they were not used to analyze the roles of the silenced genes (9,19,40,41). In a screen of siRNAs to 12 monkeypox virus ORFs, knockdown of the J5 homolog reduced the virus yield by approximately 60% (2).…”
Section: Discussionmentioning
confidence: 99%
“…One example may be the B1 kinase, which is of critical importance in the poxvirus replication cycle. A first indication for the potential of B1 as a target for antiviral therapy was demonstrated, since interfering RNAs that target B1 effectively reduced vaccinia and monkeypox virus yields and plaques in in vitro assays, especially when administered together with the proven antiviral drug cidofovir (220).…”
Section: Concluding Thoughtsmentioning
confidence: 99%